E-cadherin integrates mechanotransduction and EGFR signaling to control junctional tissue polarization and tight junction positioning. Issue 1 (December 2017) - Rübsam, Matthias; Mertz, Aaron; Kubo, Akiharu; Marg, Susanna; Jüngst, Christian; Goranci-Buzhala, Gladiola; Schauss, Astrid; Horsley, Valerie; Dufresne, Eric; Moser, Markus; Ziegler, Wolfgang; Amagai, Masayuki; et al.
Abstract Generation of a barrier in multi-layered epithelia like the epidermis requires restricted positioning of functional tight junctions (TJ) to the most suprabasal viable layer. This positioning necessitates tissue-level polarization of junctions and the cytoskeleton through unknown mechanisms. Using quantitative whole-mount imaging, genetic ablation, and traction force microscopy and atomic force microscopy, we find that ubiquitously localized E-cadherin coordinates tissue polarization of tension-bearing adherens junction (AJ) and F-actin organization to allow formation of an apical TJ network only in the uppermost viable layer. Molecularly, E-cadherin localizes and tunes EGFR activity and junctional tension to inhibit premature TJ complex formation in lower layers while promoting increased tension and TJ stability in the granular layer 2. In conclusion, our data identify an E-cadherin-dependent mechanical circuit that integrates adhesion, contractile forces and biochemical signaling to drive the polarized organization of junctional tension necessary to build an in vivo epithelial barrier. In multi-layered epithelia tight junctions (TJ) are confined to the most suprabasal viable layer. Here the authors show that this is regulated by ubiquitously localized E-cadherin tuning junctional tension and EGFR activity to inhibit TJ formation in lower layers while promoting TJ stability in the granular layer 2.